(untitled) (Al-Aasar, 2025)
Mian Muhammad Bakhash (H) was a mystic scholar who played his role in spreading Islamic teachings through his character in the subcontinent. He motivated the people to follow the right path and lead their lives remembering the world hereafter. The question arises of how he succeeded in his mission to inculcate the spirit of Islam in the people. The research has been conducted by studying the poetry of Mian Muhammad Bakhash (H-H) and analyzing the strategy that caused a change in the people. They concentrated on his message and embraced Islam. The research can conclude that Mian Muhammad Bakhash (H-H) preached to the people by conveying the message of Allah through examples of cosmology and gave a clear concept of the hereafter.